VERBAL COMMUNICATION IN ENGLISH CLASSROOM INTERACTION - Muhammad Chairil Imran; Jusmaniar N; Renita Renita (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2023)
The aim of this study is to investigate the various forms and impacts of verbal communication in the English classroom interaction between the teacher and eighth-grade students at SMPN 11 Makassar. This study employed descriptive qualitative research methodologies. The research involved a single teacher and eight students in grade 14 at SMPN 11 Makassar. The research included various instruments, including interviews, observation checklists, and video recordings, to investigate the verbal communication utilized by both teachers and students within the classroom. Furthermore, the analysis encompassed not only films but also the outcomes of discussions and interviews to examine the many forms and impacts of verbal communication. The researchers's findings in this study identified four distinct categories of verbal communication: intrapersonal, interpersonal, small group, and public communication. Additionally, the study revealed three specific effects of verbal communication: cognitive and emotional.